18F-Fluoroform: a 18F-trifluoromethylating agent for the synthesis of SCF218F-aromatic derivatives. Issue 42 (12th May 2017) - Carbonnel, Elodie; Besset, Tatiana; Poisson, Thomas; Labar, Daniel; Pannecoucke, Xavier; Jubault, Philippe
Abstract : A new protocol for the synthesis of SCF2 18 F-aromatic derivatives from 18 F-fluoroform is described. Abstract : Herein the synthesis of various SCF2 18 F-containing derivatives is reported by a transition metal-free process. By using HCF2 18 F, readily generated from a bench-stable difluoromethyl sulfonium salt, various aromatic disulfides were easily converted into the desired radiolabelled trifluoromethylthiolated compounds in the presence of a base. This protocol allowed the formation of the SCF2 18 F-containing aromatic derivatives in good to excellent radiochemical yields. This process was also extended to the corresponding selenium derivative.